Opportunistic screening to detect atrial fibrillation in Aboriginal adults in Australia. Issue 11 (15th November 2016) - Gwynne, Kylie; Flaskas, Yvonne; O'Brien, Ciaran; Jeffries, Thomas Lee; McCowen, Debbie; Finlayson, Heather; Martin, Tanya; Neubeck, Lis; Freedman, Ben
Abstract : Introduction: There is a 10-year gap in life expectancy between Aboriginal and non-Aboriginal Australians. The leading cause of death for Aboriginal Australians is cardiovascular disease, including myocardial infarction and stroke. Although atrial fibrillation (AF) is a known precursor to stroke there are no published studies about the prevalence of AF for Aboriginal people and limited evidence about AF in indigenous populations globally. Methods and analysis: This mixed methods study will recruit and train Aboriginal health workers to use an iECG device attached to a smartphone to consecutively screen 1500 Aboriginal people aged 45 years and older. The study will quantify the proportion of people who presented for follow-up assessment and/or treatment following a non-normal screening and then estimate the prevalence and age distribution of AF of the Australian Aboriginal population. The study includes semistructured interviews with the Aboriginal health workers about the effectiveness of the iECG device in their practice as well as their perceptions of the acceptability of the device for their patients. Thematic analysis will be undertaken on the qualitative data collected in the study. If the device and approach are acceptable to the Aboriginal people and widely adopted, it may help prevent the effects of untreated AF including ischaemic stroke and early deaths or impairment in Aboriginal people. Ethics and dissemination: This mixed methods study received ethics approval from the Aboriginal Health and Medical Research Council (1135/15) and the Australian Health Council of Western Australia (HREC706). Ethics approval is being sought in the Northern Territory. The findings of this study will be shared with Aboriginal communities, in peer reviewed publications and at conferences. There are Aboriginal investigators in each state/territory where the study is being conducted who have been actively involved in the study. They will also be involved in data analysis, dissemination and research translation. Trial registration number: ACTRN12616000459426 .